A polyamide-imide enameled rectangular copper wire for new energy vehicles

By adding a modified composite resin to the polyamide imide paint, the electric field distribution and dispersion are improved by using the gradient transition layer of the composite filler and the grafting of dopamine, the problems of insufficient corona resistance and degradation of tensile properties of existing enameled wires are solved, and better corona resistance is achieved.

CN118711907BActive Publication Date: 2025-03-18DONGGUAN YULONG ELECTRICIAN MATERIAL CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410893838.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-04
Publication Date
2025-03-18
Estimated Expiration
2044-07-04

AI Technical Summary

Technical Problem

The existing polyamide imide enameled flat copper wires have insufficient corona resistance under high frequency pulse voltages and their performance is degraded under tensile conditions.

Method used

By adding a modified composite resin to the polyamide imide paint, the composite resin contains a composite filler. The composite filler consists of modified boron nitride, modified graphene oxide and dopamine hydrochloride to form a gradient transition layer, improve the electric field distribution, and improve dispersion through grafting of dopamine.

Benefits of technology

The corona resistance performance of the enameled wire is improved, especially the corona resistance performance is maintained under certain stretching conditions, avoiding the negative impact of stretching on performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004928360880000111
    Figure BDA0004928360880000111
Patent Text Reader

Abstract

The invention relates to the field of polyamideimide enameled flat copper wires, and in particular to a polyamideimide enameled flat copper wire for new energy vehicles. A composite resin is added to the used polyamideimide paint, so that the polyamideimide enameled flat copper wire has good corona resistance, and still has good corona resistance under a certain stretching condition. The composite resin contains a composite filler, which is dispersed in the polyamideimide paint and exerts good anti-corona performance. The composite filler forms a gradient transition layer with different dielectric constants, thereby effectively improving the distribution of the electric field in the polyamideimide paint, so that the enameled flat copper wire has good corona resistance. At the same time, the composite filler has a certain deformation ability, thereby reducing the influence of stretching on the corona resistance of the enameled flat copper wire, and the conductive performance of graphene oxide is changed by introducing a perfluorinated segment, so as to avoid the decrease of insulation performance due to the addition of graphene oxide.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of polyamide-imide enameled rectangular copper wires, and in particular to a polyamide-imide enameled rectangular copper wire for new energy vehicles. Background Art

[0002] The core component of new energy vehicles is the variable frequency drive motor. The strong local discharge generated by the insulating enameled wire between the turns of the motor winding under the action of high-frequency pulse voltage is currently the main cause of insulation damage to the variable frequency motor. The rapid reversal of the pulse voltage of the variable frequency drive motor forms a strong reverse electric field superposition on the surface of the electromagnetic wire, and at the same time there is a tangential electric field, which makes the space charge gradually penetrate inside the medium, causing the polymer insulation layer to age. In order to adapt to the requirements of high instantaneous power, high power density, variable speed conditions, strong overload capacity and large starting torque, the enameled wire needs to have good corona resistance.

[0003] At present, the commonly used method to improve the corona resistance of enameled wire is to add inorganic fillers to the polyamide-imide paint base material. The addition of inorganic fillers can effectively improve the corona resistance of the enameled wire. However, during the production and manufacturing process of the motor insulation system, the enameled wire will be stretched to a certain extent, resulting in a decrease in the thickness of the polyamide-imide paint layer, which in turn leads to a decrease in the corona resistance of the enameled wire. Therefore, there is a need for an enameled wire that still has good corona resistance under a certain degree of stretching. Summary of the invention

[0004] The purpose of the present invention is to provide a polyamide-imide enameled rectangular copper wire for new energy vehicles, which solves the problem of insufficient corona resistance of the existing polyamide-imide enameled rectangular copper wire, and at the same time still has good corona resistance under certain stretching conditions.

[0005] The purpose of the present invention can be achieved by the following technical scheme: a polyamideimide enameled rectangular copper wire for new energy vehicles, which is prepared by the following steps: feeding a flat copper core into an enameling machine, first coating it with a modified polyamideimide paint, the number of coating layers is 6 layers, drying and curing, and then coating it with a self-lubricating enameled wire paint, the number of coating layers is 2 layers, and winding to obtain a polyamideimide enameled rectangular copper wire for new energy vehicles;

[0006] The modified polyamide-imide paint is prepared by the following steps: weighing the following raw materials by weight: 15-20 parts of composite resin and 20-25 parts of polyamide-imide paint, mixing the composite resin and the polyamide-imide paint at a temperature of 50-60° C. to prepare the modified polyamide-imide paint;

[0007] The composite resin is prepared by the following steps:

[0008] Step A1: Mix hexagonal boron nitride and ethanol and ultrasonically disperse for 10-12 hours to obtain liquid A, mix tetrabutyl titanate, anhydrous ethanol and glacial acetic acid, stir for 30 minutes at a stirring rate of 300-400 rpm at room temperature to obtain liquid B, slowly drip liquid B into liquid A, stir for 5-6 hours at a stirring rate of 200-300 rpm at room temperature, age for 12 hours, dry at 80°C for 12 hours, and calcine at 400°C for 2.5 hours to obtain supported boron nitride;

[0009] The dosage ratio of hexagonal boron nitride and ethanol is 0.3-0.5g:100-120mL, the dosage ratio of tetrabutyl titanate, anhydrous ethanol and glacial acetic acid is 10-12mL:40-45mL:2-3mL, and the dosage ratio of liquid A and liquid B is 100-120mL:50-60mL;

[0010] During the reaction, under the action of ultrasound, hexagonal boron nitride is peeled off to form boron nitride nanosheets, and then titanium dioxide is loaded on the boron nitride nanosheets through a sol-gel method using tetrabutyl titanate as a titanium source and calcined to obtain loaded boron nitride.

[0011] Step A2: Modified graphene oxide, loaded boron nitride and tetrahydrofuran are mixed, and ultrasonically dispersed for 8-10 hours at room temperature, and then Tris buffer and deionized water are added, and then dopamine hydrochloride is added at a stirring rate of 200-300 rpm and room temperature, and reacted for 3-4 hours to obtain a precursor 1;

[0012] The ratio of modified graphene oxide, loaded boron nitride, Tris buffer and dopamine hydrochloride is 3-4 g: 4-6 g: 5-6 g: 1-1.2 g;

[0013] During the reaction, under the action of ultrasound, due to the π-π interaction between the grafted aniline trimer in the modified graphene oxide and the boron nitride in the supported boron nitride, the modified graphene oxide and the supported boron nitride are stacked in a non-covalent bond phase to form a layered structure, and then dopamine hydrochloride is added for modification, and dopamine is grafted on the surface to obtain a composite filler;

[0014] Step A3: the composite filler and N,N-dimethylacetamide are mixed and ultrasonically dispersed for 1.5-2 hours, and 4,4'-diaminodiphenyl ether and pyromellitic anhydride are added under stirring at a rate of 300-400 rpm and room temperature, and the mixture is reacted for 3-4 hours to obtain a composite resin;

[0015] The usage ratio of composite filler, N,N-dimethylacetamide, 4,4'-diaminodiphenyl ether and pyromellitic acid dianhydride is 0.45-0.5g:40mL:2.8-3g:4-5g;

[0016] During the reaction, the amino groups in the grafted dopamine in the composite filler react with the amino groups in 4,4'-diaminodiphenyl ether and the anhydride groups in pyromellitic dianhydride to form amide groups, thereby obtaining a composite resin;

[0017] The modified graphene oxide is prepared by the following steps:

[0018] Step B1: Aniline, 4,4'-diaminodiphenylamine sulfate hydrate, sodium chloride and deionized water are mixed, and ammonium persulfate and hydrochloric acid solution are added under stirring at a rate of 300-400 rpm and a temperature of -5°C, and the mixture is reacted for 1-1.5 hours to obtain an aniline trimer; the aniline trimer, 4-perfluorohexylaniline and tetrahydrofuran are mixed, and the mixture is reacted for 3-4 hours under stirring at a rate of 300-400 rpm and a temperature of 40°C to obtain an intermediate a;

[0019] The molar concentration of the hydrochloric acid solution is 1 mol / L, the dosage ratio of aniline, 4,4'-diaminodiphenylamine sulfate hydrate, sodium chloride, ammonium persulfate and hydrochloric acid solution is 0.8-0.81 mol: 0.8-0.81 mol: 70-75 g: 0.8 mol: 200 mL, and the dosage ratio of aniline trimer and 4-perfluorohexylaniline is 2.2-2.5 g: 0.02-0.021 mol;

[0020] During the reaction, under the action of ammonium persulfate, aniline and 4,4'-diaminodiphenylamine sulfate hydrate undergo polymerization to obtain aniline trimer, and the aniline trimer then reacts with 4-perfluorohexylaniline to obtain intermediate a;

[0021] Step B2: The intermediate a, graphene oxide and N,N-dimethylformamide are mixed and ultrasonically dispersed for 20-30 minutes, and 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide and N-hydroxysuccinimide are added under stirring at a stirring rate of 200-300 rpm and room temperature, and the reaction is carried out for 4-6 hours to obtain modified graphene oxide;

[0022] The ratio of intermediate a, graphene oxide, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide and N-hydroxysuccinimide is 0.07-0.072 mol: 0.4-0.5 g: 0.002 mol: 0.002 mol;

[0023] During the reaction, under the action of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide and N-hydroxysuccinimide, the amino group in the intermediate a and the carboxyl group in the graphene oxide undergo an amidation reaction, and the aniline trimer is grafted onto the graphene oxide to obtain modified graphene oxide;

[0024] Beneficial effects of the invention: The invention discloses a polyamideimide enameled rectangular copper wire for new energy vehicles. By adding a composite resin to the polyamideimide paint used, the polyamideimide enameled rectangular copper wire has good corona resistance, and at the same time, it still has good corona resistance under a certain stretching condition. The composite resin contains a composite filler. Since dopamine is grafted onto the outside of the composite filler, the surface polarity of the composite filler is changed, so that the composite filler can be better dispersed in the composite resin, and then evenly dispersed in the polyamideimide paint, and its good anti-corona performance is exerted. Since the modified boron nitride in the composite filler is loaded with nano titanium dioxide, and there is a certain difference in the dielectric constants of titanium dioxide, boron nitride and graphene, the composite filler forms a gradient transition layer. This effectively improves the distribution of the electric field in the polyamide-imide paint, so that the enameled flat copper wire has good corona resistance. At the same time, since the amino group in the dopamine grafted on the surface of the composite filler reacts with the anhydride group in the pyromellitic dianhydride, when the enameled flat copper wire is stretched by an external force, the external force is transmitted to the composite filler. Since the composite filler is made by linking modified boron nitride and modified graphene through non-covalent bonds, the composite filler has a certain deformation ability, which allows the composite filler to deform with the stretching when an external force acts, thereby reducing the influence of stretching on the corona resistance of the enameled flat copper wire. The perfluorinated chain segment is introduced into the graphene oxide through the intermediate a, which changes the conductive properties of the graphene oxide to a certain extent, thereby avoiding the degradation of the insulation performance due to the addition of graphene oxide. DETAILED DESCRIPTION

[0025] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0026] Example 1 A polyamideimide enameled rectangular copper wire for new energy vehicles is prepared by the following steps: feeding a flat copper core into an enameling machine, first coating it with a modified polyamideimide paint, the number of coating layers is 6 layers, drying and curing, and then coating it with a commercially available DF-43 self-lubricating enameled wire paint, the number of coating layers is 2 layers, and winding to obtain a polyamideimide enameled rectangular copper wire for new energy vehicles;

[0027] The modified polyamide-imide paint is prepared by the following steps: weighing the following raw materials by weight: 15 parts of a composite resin and 20 parts of a commercially available DF-1760 polyamide-imide paint, mixing the composite resin and the polyamide-imide paint at a temperature of 50° C. to prepare a modified polyamide-imide paint;

[0028] The composite resin is prepared by the following steps:

[0029] Step A1: Mix commercially available XFNAN XF101 hexagonal boron nitride and ethanol and ultrasonically disperse for 10 hours to obtain liquid A, mix tetrabutyl titanate, anhydrous ethanol and glacial acetic acid, stir for 30 minutes at a stirring rate of 300 rpm at room temperature to obtain liquid B, slowly drop liquid B into liquid A, stir for 5 hours at a stirring rate of 200 rpm at room temperature, age for 12 hours, dry at 80°C for 12 hours, and calcine at 400°C for 2.5 hours to obtain supported boron nitride;

[0030] The dosage ratio of hexagonal boron nitride and ethanol is 0.3 g:100 mL, the dosage ratio of tetrabutyl titanate, anhydrous ethanol and glacial acetic acid is 10 mL:40 mL:2 mL, and the dosage ratio of liquid A and liquid B is 100 mL:50 mL;

[0031] Step A2: Modified graphene oxide, loaded boron nitride and tetrahydrofuran were mixed, and ultrasonically dispersed for 8 hours at room temperature, and then Tris buffer and deionized water were added, and then dopamine hydrochloride was added at a stirring rate of 200 rpm and room temperature, and reacted for 3 hours to obtain a precursor 1;

[0032] The ratio of modified graphene oxide, loaded boron nitride, Tris buffer and dopamine hydrochloride is 3 g: 4 g: 5 g: 1 g;

[0033] Step A3: the composite filler and N,N-dimethylacetamide were mixed and ultrasonically dispersed for 1.5 hours, and 4,4'-diaminodiphenyl ether and pyromellitic anhydride were added under stirring at a stirring rate of 300 rpm and room temperature, and the mixture was reacted for 3 hours to obtain a composite resin;

[0034] The usage ratio of composite filler, N,N-dimethylacetamide, 4,4'-diaminodiphenyl ether and pyromellitic dianhydride is 0.45g:40mL:2.8g:4g;

[0035] The modified graphene oxide is prepared by the following steps:

[0036] Step B1: Aniline, 4,4'-diaminodiphenylamine sulfate hydrate, sodium chloride and deionized water are mixed, and ammonium persulfate and hydrochloric acid solution are added under stirring at a rate of 300 rpm and a temperature of -5°C, and the mixture is reacted for 1 hour to obtain an aniline trimer; the aniline trimer, 4-perfluorohexylaniline and tetrahydrofuran are mixed, and the mixture is reacted for 3 hours under stirring at a rate of 300 rpm and a temperature of 40°C to obtain an intermediate a;

[0037] The molar concentration of the hydrochloric acid solution is 1 mol / L, the amount ratio of aniline, 4,4'-diaminodiphenylamine sulfate hydrate, sodium chloride, ammonium persulfate and hydrochloric acid solution is 0.8 mol: 0.8 mol: 70 g: 0.8 mol: 200 mL, and the amount ratio of aniline trimer and 4-perfluorohexylaniline is 2.2 g: 0.02 mol;

[0038] Step B2: Intermediate a, commercially available XFNAN XFSG01 graphene oxide and N,N-dimethylformamide were mixed and ultrasonically dispersed for 20 minutes, and 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide and N-hydroxysuccinimide were added under stirring at a stirring rate of 200 rpm and room temperature, and reacted for 4 hours to obtain modified graphene oxide;

[0039] The usage ratio of intermediate a, graphene oxide, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide and N-hydroxysuccinimide is 0.07 mol: 0.4 g: 0.002 mol: 0.002 mol.

[0040] Example 2 A polyamideimide enameled rectangular copper wire for new energy vehicles is prepared by the following steps: feeding a flat copper core into an enameling machine, first coating it with a modified polyamideimide paint, the number of coating layers is 6 layers, drying and curing, and then coating it with a commercially available DF-43 self-lubricating enameled wire paint, the number of coating layers is 2 layers, and winding to obtain a polyamideimide enameled rectangular copper wire for new energy vehicles;

[0041] The modified polyamide-imide paint is prepared by the following steps: weighing the following raw materials by weight: 20 parts of composite resin and 20 parts of commercially available DF-1760 polyamide-imide paint, mixing the composite resin and the polyamide-imide paint at a temperature of 60° C. to prepare the modified polyamide-imide paint;

[0042] The composite resin is prepared by the following steps:

[0043] Step A1: Mix commercially available XFNAN XF101 hexagonal boron nitride and ethanol and ultrasonically disperse for 10 hours to obtain liquid A, mix tetrabutyl titanate, anhydrous ethanol and glacial acetic acid, stir for 30 minutes at a stirring rate of 400 rpm at room temperature to obtain liquid B, slowly drop liquid B into liquid A, stir for 6 hours at a stirring rate of 300 rpm at room temperature, age for 12 hours, dry at 80°C for 12 hours, and calcine at 400°C for 2.5 hours to obtain supported boron nitride;

[0044] The dosage ratio of hexagonal boron nitride to ethanol is 0.5 g:120 mL, the dosage ratio of tetrabutyl titanate, anhydrous ethanol and glacial acetic acid is 12 mL:45 mL:3 mL, and the dosage ratio of liquid A to liquid B is 120 mL:50 mL;

[0045] Step A2: Modified graphene oxide, loaded boron nitride and tetrahydrofuran were mixed, and ultrasonically dispersed for 8 hours at room temperature, and then Tris buffer and deionized water were added, and then dopamine hydrochloride was added at a stirring rate of 300 rpm and room temperature, and reacted for 4 hours to obtain a precursor 1;

[0046] The ratio of modified graphene oxide, loaded boron nitride, Tris buffer and dopamine hydrochloride is 3 g: 4 g: 5 g: 1 g;

[0047] During the reaction, under the action of ultrasound, due to the π-π interaction between the grafted aniline trimer in the modified graphene oxide and the boron nitride in the supported boron nitride, the modified graphene oxide and the supported boron nitride are stacked in a non-covalent bond phase to form a layered structure, and then dopamine hydrochloride is added for modification, and dopamine is grafted on the surface to obtain a composite filler;

[0048] Step A3: the composite filler and N,N-dimethylacetamide were mixed and ultrasonically dispersed for 2 hours, and 4,4'-diaminodiphenyl ether and pyromellitic anhydride were added under stirring at a stirring rate of 300 rpm and room temperature, and the mixture was reacted for 4 hours to obtain a composite resin;

[0049] The usage ratio of composite filler, N,N-dimethylacetamide, 4,4'-diaminodiphenyl ether and pyromellitic dianhydride is 0.45g:40mL:2.8g:5g;

[0050] The modified graphene oxide is prepared by the following steps:

[0051] Step B1: Aniline, 4,4'-diaminodiphenylamine sulfate hydrate, sodium chloride and deionized water are mixed, and ammonium persulfate and hydrochloric acid solution are added under stirring at a rate of 400 rpm and a temperature of -5°C, and the mixture is reacted for 1.5 hours to obtain an aniline trimer; the aniline trimer, 4-perfluorohexylaniline and tetrahydrofuran are mixed, and the mixture is reacted for 3 hours under stirring at a rate of 400 rpm and a temperature of 40°C to obtain an intermediate a;

[0052] The molar concentration of the hydrochloric acid solution is 1 mol / L, the amount ratio of aniline, 4,4'-diaminodiphenylamine sulfate hydrate, sodium chloride, ammonium persulfate and hydrochloric acid solution is 0.8 mol: 0.81 mol: 75 g: 0.8 mol: 200 mL, and the amount ratio of aniline trimer and 4-perfluorohexylaniline is 2.5 g: 0.02 mol;

[0053] Step B2: Intermediate a, commercially available XFNAN XFSG01 graphene oxide and N,N-dimethylformamide were mixed and ultrasonically dispersed for 20 minutes, and 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide and N-hydroxysuccinimide were added under stirring at a stirring rate of 300 rpm and room temperature, and the mixture was reacted for 6 hours to obtain modified graphene oxide;

[0054] The usage ratio of intermediate a, graphene oxide, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide and N-hydroxysuccinimide is 0.07 mol: 0.5 g: 0.002 mol: 0.002 mol.

[0055] Example 3 A polyamideimide enameled rectangular copper wire for new energy vehicles is prepared by the following steps: feeding a flat copper core into an enameling machine, first coating it with a modified polyamideimide paint, the number of coating layers is 6 layers, drying and curing, and then coating it with a commercially available DF-43 self-lubricating enameled wire paint, the number of coating layers is 2 layers, and winding to obtain a polyamideimide enameled rectangular copper wire for new energy vehicles;

[0056] The modified polyamide-imide paint is prepared by the following steps: weighing the following raw materials by weight: 20 parts of composite resin and 25 parts of commercially available DF-1760 polyamide-imide paint, mixing the composite resin and the polyamide-imide paint at a temperature of 60° C. to prepare the modified polyamide-imide paint;

[0057] The composite resin is prepared by the following steps:

[0058] Step A1: Mix commercially available XFNAN XF101 hexagonal boron nitride and ethanol and ultrasonically disperse for 12 hours to obtain liquid A, mix tetrabutyl titanate, anhydrous ethanol and glacial acetic acid, stir for 30 minutes at a stirring rate of 400 rpm and room temperature to obtain liquid B, slowly drop liquid B into liquid A, stir for 6 hours at a stirring rate of 300 rpm and room temperature, age for 12 hours, dry at 80°C for 12 hours, and calcine at 400°C for 2.5 hours to obtain supported boron nitride;

[0059] The dosage ratio of hexagonal boron nitride to ethanol is 0.5 g:120 mL, the dosage ratio of tetrabutyl titanate, anhydrous ethanol and glacial acetic acid is 12 mL:45 mL:3 mL, and the dosage ratio of liquid A to liquid B is 120 mL:60 mL;

[0060] Step A2: Modified graphene oxide, loaded boron nitride and tetrahydrofuran were mixed, and ultrasonically dispersed for 10 hours at room temperature, and then Tris buffer and deionized water were added, and then dopamine hydrochloride was added at a stirring rate of 300 rpm and room temperature, and reacted for 4 hours to obtain a precursor 1;

[0061] The ratio of modified graphene oxide, loaded boron nitride, Tris buffer and dopamine hydrochloride is 4 g: 6 g: 6 g: 1.2 g;

[0062] Step A3: the composite filler and N,N-dimethylacetamide were mixed and ultrasonically dispersed for 2 hours, and 4,4'-diaminodiphenyl ether and pyromellitic dianhydride were added under stirring at a stirring rate of 400 rpm and room temperature, and the mixture was reacted for 4 hours to obtain a composite resin;

[0063] The usage ratio of composite filler, N,N-dimethylacetamide, 4,4'-diaminodiphenyl ether and pyromellitic dianhydride is 0.5g:40mL:3g:5g;

[0064] The modified graphene oxide is prepared by the following steps:

[0065] Step B1: Aniline, 4,4'-diaminodiphenylamine sulfate hydrate, sodium chloride and deionized water are mixed, and ammonium persulfate and hydrochloric acid solution are added under stirring at a rate of 400 rpm and a temperature of -5°C, and the mixture is reacted for 1.5 hours to obtain an aniline trimer; the aniline trimer, 4-perfluorohexylaniline and tetrahydrofuran are mixed, and the mixture is reacted for 4 hours under stirring at a rate of 400 rpm and a temperature of 40°C to obtain an intermediate a;

[0066] The molar concentration of the hydrochloric acid solution is 1 mol / L, the amount ratio of aniline, 4,4'-diaminodiphenylamine sulfate hydrate, sodium chloride, ammonium persulfate and hydrochloric acid solution is 0.81 mol: 0.81 mol: 75 g: 0.8 mol: 200 mL, and the amount ratio of aniline trimer and 4-perfluorohexylaniline is 2.5 g: 0.021 mol;

[0067] Step B2: Intermediate a, commercially available XFNAN XFSG01 graphene oxide and N,N-dimethylformamide were mixed and ultrasonically dispersed for 30 minutes, and 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide and N-hydroxysuccinimide were added under stirring at a stirring rate of 300 rpm and room temperature, and the mixture was reacted for 6 hours to obtain modified graphene oxide;

[0068] The usage ratio of intermediate a, graphene oxide, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide and N-hydroxysuccinimide is 0.072 mol: 0.5 g: 0.002 mol: 0.002 mol.

[0069] Comparative Example 1 Compared with Example 3, this comparative example is different in that the boron nitride loaded in the composite resin preparation process of Example 3 is replaced by boron nitride nanosheets, and the other steps are the same.

[0070] Comparative Example 2 Compared with Example 3, this comparative example is to remove dopamine hydrochloride in the preparation process of the composite resin in Example 3, and the other steps are the same.

[0071] Comparative Example 3 Compared with Example 3, this comparative example is characterized in that 4-perfluorohexylaniline in the preparation process of modified graphene oxide in Example 3 is replaced by aniline, and the other steps are the same.

[0072] Comparative Example 4 Compared with Example 3, this comparative example is different in that the composite resin in Example 3 is replaced by commercially available DF-1760 polyamide-imide paint, and the other steps are the same.

[0073] Take a polyamide-imide enameled rectangular copper wire for new energy vehicles prepared in Example 1, Example 2, Example 3, Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4, cut it into a sample with an effective straight length of 120 mm, an angle of 60°, and a length of 40 mm at both ends, and refer to GB / T4074.5-2008 and GB / T 21707-2018. The corona resistance performance is tested, the voltage is 3 kV, the pulse frequency is 20 kHz, the pulse duty cycle is 50%, the pulse waveform is a square wave, the pulse polarity is bipolar, the test temperature is 155±2°C, and the corona resistance time is recorded. The sample is stretched, and the corona resistance time under the conditions of stretching rate of 5% and 15% is measured, and the corona resistance time retention rate is calculated. The test results are as follows:

[0074]

[0075] It can be seen from the test results in the table shown that Example 1, Example 2 and Example 3 are compared with Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4. Comparative Example 1 replaces the boron nitride loaded in the preparation process of the composite resin in Example 3 with boron nitride nanosheets. Due to the lack of titanium dioxide, its corona resistance is greatly reduced. Comparative Example 2 removes dopamine hydrochloride in the preparation process of the composite resin in Example 3. Due to the lack of dopamine grafting, its dispersion ability is reduced, thereby affecting its corona resistance. Comparative Example 3 replaces 4-perfluorohexylaniline with aniline in the preparation process of modified graphene oxide in Example 3. Due to the lack of perfluorinated segments, the properties of graphene oxide itself have a certain influence on the corona resistance. Comparative Example 4 replaces the modified polyamide-imide paint in Example 3 with polyamide-imide paint, and its corona resistance under stretching conditions is significantly reduced.

[0076] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0077] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.

Claims

1. A polyamide-imide enameled rectangular copper wire for new energy vehicles, characterized in that: The method is as follows: feeding a flat copper core into an enameling machine, first coating it with a modified polyamide-imide paint, the coating number is 6 layers, drying and curing, then coating it with a self-lubricating enameled wire paint, the coating number is 2 layers, and winding, to obtain a polyamide-imide enameled flat copper wire for new energy vehicles; The modified polyamide-imide paint is prepared by the following steps: weighing the following raw materials by weight: 15-20 parts of composite resin and 20-25 parts of polyamide-imide paint, mixing the composite resin and the polyamide-imide paint at a temperature of 50-60° C. to prepare the modified polyamide-imide paint; The composite resin is prepared by the following steps: Step A1: Mix hexagonal boron nitride and ethanol and ultrasonically disperse for 10-12 hours to obtain liquid A, mix tetrabutyl titanate, anhydrous ethanol and glacial acetic acid, stir for 30 minutes at a stirring rate of 300-400 rpm at room temperature to obtain liquid B, slowly drip liquid B into liquid A, stir for 5-6 hours at a stirring rate of 200-300 rpm at room temperature, age for 12 hours, dry at 80°C for 12 hours, and calcine at 400°C for 2.5 hours to obtain supported boron nitride; Step A2: Modified graphene oxide, loaded boron nitride and tetrahydrofuran are mixed, and ultrasonically dispersed for 8-10 hours at room temperature, and then Tris buffer and deionized water are added, and then dopamine hydrochloride is added at a stirring rate of 200-300 rpm and room temperature, and reacted for 3-4 hours to obtain a precursor 1; Step A3: Precursor 1 and N,N-dimethylacetamide are mixed and ultrasonically dispersed for 1.5-2 hours, and 4,4'-diaminodiphenyl ether and pyromellitic anhydride are added under stirring at a rate of 300-400 rpm and room temperature, and reacted for 3-4 hours to obtain a composite resin; The modified graphene oxide is prepared by the following steps: Step B1: Aniline, 4,4'-diaminodiphenylamine sulfate hydrate, sodium chloride and deionized water are mixed, and ammonium persulfate and hydrochloric acid solution are added under stirring at a rate of 300-400 rpm and a temperature of -5°C, and the mixture is reacted for 1-1.5 hours to obtain an aniline trimer; the aniline trimer, 4-perfluorohexylaniline and tetrahydrofuran are mixed, and the mixture is reacted for 3-4 hours under stirring at a rate of 300-400 rpm and a temperature of 40°C to obtain an intermediate a; Step B2: The intermediate a, graphene oxide and N,N-dimethylformamide are mixed and ultrasonically dispersed for 20-30 minutes. At a stirring rate of 200-300 rpm and room temperature, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide and N-hydroxysuccinimide are added and reacted for 4-6 hours to obtain modified graphene oxide.

2. The polyamide-imide enameled rectangular copper wire for new energy vehicles according to claim 1, characterized in that: In step A1, the ratio of hexagonal boron nitride to ethanol is 0.3-0.5 g: 100-120 mL, the ratio of tetrabutyl titanate, anhydrous ethanol and glacial acetic acid is 10-12 mL: 40-45 mL: 2-3 mL, and the ratio of liquid A to liquid B is 100-120 mL: 50-60 mL.

3. The polyamide-imide enameled rectangular copper wire for new energy vehicles according to claim 1, characterized in that: In step A2: the ratio of modified graphene oxide, loaded boron nitride, Tris buffer and dopamine hydrochloride is 3-4 g: 4-6 g: 5-6 g: 1-1.2 g.

4. The polyamide-imide enameled rectangular copper wire for new energy vehicles according to claim 1, characterized in that: In step A3: the ratio of the precursor 1, N,N-dimethylacetamide, 4,4'-diaminodiphenyl ether and pyromellitic dianhydride is 0.45-0.5 g: 40 mL: 2.8-3 g: 4-5 g.

5. The polyamide-imide enameled rectangular copper wire for new energy vehicles according to claim 1, characterized in that: In step B1: the molar concentration of the hydrochloric acid solution is 1 mol / L, the amount ratio of aniline, 4,4'-diaminodiphenylamine sulfate hydrate, sodium chloride, ammonium persulfate and hydrochloric acid solution is 0.8-0.81 mol: 0.8-0.81 mol: 70-75 g: 0.8 mol: 200 mL, and the amount ratio of aniline trimer and 4-perfluorohexylaniline is 2.2-2.5 g: 0.02-0.021 mol.

6. The polyamide-imide enameled rectangular copper wire for new energy vehicles according to claim 1, characterized in that: In step B2: the ratio of intermediate a, graphene oxide, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide and N-hydroxysuccinimide is 0.07-0.072 mol: 0.4-0.5 g: 0.002 mol: 0.002 mol.

Citation Information

Patent Citations

  • Polydopamine modified carbon nanotube graphene / polyimide composite material and preparation method thereof

    CN108276577A

  • Insulating film

    CN109155165A